2016
DOI: 10.3897/italianbotanist.1.8818
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers for the Italian flora: 1

Abstract: In this contribution new chromosome data obtained on material collected in Italy are presented. It includes 15 chromosome counts for Carduus, Crepis, Picris, Taraxacum (Asteraceae), Ceratonia, Lathyrus (Fabaceae), Colchicum (Colchicaceae), Fritillaria (Liliaceae), Petrorhagia (Caryophyllaceae), Potentilla (Rosaceae), Quercus (Fagaceae), Reseda (Resedaceae), and Thymus (Lamiaceae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is found on the main tectonic-karst high plateaus in Abruzzo (Tenore 1831-42;Pedrotti 1969;Tammaro 1971;Anzalone and Veri 1975;Pignatti 1982Pignatti , 2017Pirone 1987b;Conti 1992b;Conti 1998;Conti and Bartolucci 2016). The population growing in Altopiano delle Rocche was recently analysed also from a molecular and karyological (2n = 14) point of view (Schlee et al 2011;Peruzzi et al 2016) and needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is found on the main tectonic-karst high plateaus in Abruzzo (Tenore 1831-42;Pedrotti 1969;Tammaro 1971;Anzalone and Veri 1975;Pignatti 1982Pignatti , 2017Pirone 1987b;Conti 1992b;Conti 1998;Conti and Bartolucci 2016). The population growing in Altopiano delle Rocche was recently analysed also from a molecular and karyological (2n = 14) point of view (Schlee et al 2011;Peruzzi et al 2016) and needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…sub: Thalictrum aquilegiifolium L. − Ref. : Caruel 1860;Marcucci 1889;Baroni 1897Baroni -1908Pichi Sermolli 1948;Zangheri 1966a;Zangheri 1966b;Matteini 1968;Siemoni et al 1989Siemoni et al -1998Chiosi 1990;Falzea 2006;Mazza 2006;Zingarelli 2006;Mazza et al 2008;Frignani et al 2009b Baroni 1897Baroni -1908Siemoni et al 1989Siemoni et al -1998Chiosi 1990;Peruzzi et al 2016a− Exs. : 1987…”
Section: Vicia Pseudocraccamentioning
confidence: 99%
“…Moreover, due to this paucity of genomic information, there are only speculations regarding the genome size of C. siliqua (Bureš et al 2004). It is reported that the number of chromosomes of carob are 2n=24 (de Almeida, 1948; Frahm-Leliveld, 1957; Berger et al, 1958; Goldblatt, 1981; Yeh et al, 1986; Arista and Talavera, 1990; Rice et al 2015; Peruzzi et al 2016). It is also known that carob tree is diploid, even though some cases of triploidy and tetraploidy have been found (Bureš et al 2004).…”
Section: Introductionmentioning
confidence: 99%